Discussion of R. H. Douglas' Recent hailstorm research: a review - Schleusener, Richard A., author; Civil Engineering Section, Colorado State University, publisher (Colorado State University. Libraries, 1962)
Research on hailstorms is hampered by the fact that quantitative climatological data on hail events are limited. Recent research studies have developed new techniques to obtain such quantitative data, including use of passive recorders for recording characteristics of hailfalls. Through use of such equipment in Colorado hail studies, it was found that while hailstorms with large stones are spectacular, they are relatively rare. Most of the crop damage from hail in Colorado probably results from hailstones smaller than 1. 5 cm diameter. Hailstone crystal structure from Colorado hailstones suggests an average process by which the stones form at warm temperatures, then grow to radii of 2 to 3 cm in a "dry" environment, and finally grow to radii in excess of 3 cm in a "wet" environment. It was found that successively larger fractions of the total volume of hail were formed in a "wet" environment as the season progressed from May to July. It was found that conventional hail forecasting techniques suffer an inability to distinguish clearly between severe hail and heavy rain. The occurrence of strong winds aloft was found to be associated with severe hail.
CER62RAS9.
Prepared for American Meteorological Society Conference on Severe Storms, Norman, Oklahoma, 13 February 1962.
Keywords: Hailstorms; Hail; Rain and rainfall